A2.35 TRNT1 missense mutations define a new periodic fever syndrome. (13th February 2015) - Giannelou, A Angeliki; Zhou, Q; Stoffels, M; Ombrello, A; Stone, D; Edwan, JH; Pelletier, M; Tsai, W; Calvo, K; Rosenzweig, S; Barron, K; Gadina, M; et al.
Abstract : Background: Two thirds of the 1700 patients seen at our NIH clinic for autoinflammatory diseases do not have a genetic diagnosis. Whole exome sequencing permits analysis of most of the protein coding regions of the human genome. Methods: With the use of whole exome sequencing and candidate gene screening, we identified five children from four unrelated families, who had unexplained autoinflammatory disease and shared mutations in one common gene. One family from Saudi Arabia was consanguineous with two affected daughters. The second family of mixed Czech and British background had one affected boy. The third and fourth families were of mixed European ancestry from the United States and each family had one affected daughter. We performed additional experiments in patients samples including flow cytometry, immunophenotyping, cytokine profiling, mitochondria related function and ribosomal assembly assays. Protein function was studied with morpholino knockdowns in zebrafish embryos. Results: All patients carried missense recessive mutations in one common gene, the TRNT1 (tRNA Nucleotidyl Transferase, CCA-Adding, 1), on chromosome 3. The two affected Saudi Arabian sisters were homozygous for a p. H215R missense mutation, while the other three children were compound heterozygous for a missense mutation, p. I223T or p. R99W, and one shared mutation p. D163V. The p. H215R mutation was not found in any public database neither in 1061 Arab control DNA samples. From the three Caucasian mutations, the p. R99W was novel whereas the p. I223T and p. D163V were found at a very low allele frequency (<0.001) at the NHLBI exomedatabase. All mutations affect highly conserved amino acid residues and are predicted to be damaging to the protein function. All children had recurrent episodes of high fevers with negative sepsis work up that occurred in association with microcytic anaemia, and a spectrum of multisystem features. Neurologic involvement ranged from mild developmental delay to nystagmus, hypotonia, optic nerve atrophy, and sensorineural hearing loss. Other variables manifestations include dysmorphic features, musculoskeletal and gastrointestinal symptoms, B cell immunodeficiency and hypogammaglobulinemia. Studies performed so far, point towards a maturation defect of the B cell lineage in the bone marrow, as a possible cause of the observed immunodeficiency. Preliminary data from cytokine analysis in two patients have shown elevated levels of the proinflammatory cytokines interleukin 6 and type 1interferon, suggesting possible therapeutic targets. Knockdown of the zebrafish TRNT1 homologue caused hydrocephaly, defects in tail development, anaemia and a reduction in the number of hair cells present in the lateral line, that has function resembling human inner ear. Conclusion: The CCA-adding TRNT1 enzyme catalyses the addition of the CCA terminus to the 3 prime end of all tRNAs precursors, a step that is essential for tRNA aminoacylation and protein synthesis. The discovery that missense mutations in this essential and ubiquitiously expressed gene cause a newly defined periodic fever syndrome, will allow further understanding of mechanisms underlying inflammation.